The Role of Profitability as a Mediating Variable in the Relationship between Sustainability Reporting and Firm Value in Islamic Commercial Banks in Indonesia - Rinna Ramadhan Ain Fitriah; Samsul Muhammad La Ane (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This study addresses the inconsistency of prior empirical findings regarding the effect of sustainability reporting on firm value, particularly in the Islamic banking sector where financial indicators remain dominant in investment decisions. The significance of this research lies in providing a clearer understanding of how sustainability practices contribute to firm value. Therefore, this study aims to examine the role of financial performance as a mediating variable in the relationship between sustainability reporting and firm value in Islamic commercial banks in Indonesia. Methods: This research employs a causal quantitative approach using panel data from 10 Islamic commercial banks over the 2022–2024 period. Data are obtained from annual reports, sustainability reports, and financial statements. The analysis was conducted using panel data regression and the Sobel test to examine the mediating effect. Results: The findings indicate that sustainability reporting has a positive effect on financial performance. In addition, financial performance significantly enhances firm value and acts as a mediating variable in the relationship between sustainability reporting and firm value. Conclusion and suggestion: The results confirm that sustainability practices contribute to firm value indirectly through financial performance. Therefore, Islamic commercial banks are encouraged to strengthen the quality of sustainability reporting as a strategic effort to improve firm value and maintain long-term performance.